Evaluation of The Monitoring Of Licensing Services For The Issuance of Business Identification Numbers at The Public Service Mall Dpmptsp Jombang Regency - Utami, Siska; Mustofa, Amirul; Sedarmayanti , Sedarmayanti (PT. Anagata Sembagi Education, 2025)
The licensing service for the issuance of Business Identification Number (NIB) at the Public Service Mall (PSM) DPMPTSP Jombang Regency is an integrated service that facilitates business actors in obtaining business legality through the Online Single Submission (OSS) system. The goal is to provide convenience, speed, and legal certainty for the community in starting a business, as well as supporting the investment climate and regional economic growth in an efficient and transparent manner. The purpose of this study is to assess the effectiveness of the service of issuing Business Identification Numbers (NIB) at the DPMPTSP Public Service Mall in Jombang Regency, including the quality of service, obstacles faced, level of community satisfaction, and the impact of services on business legality and ease of doing business in the area. The research method used is qualitative with a descriptive approach. The Goal-Based Evaluation Theory was first developed by Michael Scriven, with the following indicators: (i) Time Efficiency, (ii) Quality of Service, (iii) Process Efficiency, (iv) Inter-Agency Coordination, (v) Compliance to Standards and Regulations, (vi) Impact of the Program. The results of the study show that NIB services at PSM Jombang run effectively with fast service times and high community satisfaction (IKM 91.08). Services are assessed both in terms of cost, officer attitude, and complaints. However, there are still constraints on turnaround times, complicated procedures, and OSS system disruptions. The solution for its sustainability is the need to simplify procedures, improve human resources and OSS systems, socialize more widely, and strengthen coordination between agencies to speed up the service process.